Use of Complementary Therapies Among Primary Care Clinic Patients With Arthritis - Carla J. Herman; Peg Allen; William C. Hunt; Arti Prasad; Teresa J. Brady (Preventing Chronic Disease, 2004)
Introduction Use of complementary and alternative medicine (CAM) for chronic conditions has increased in recent years. There is little information, however, on CAM use among adults with clinic-confirmed diagnoses, including arthritis, who are treated by primary care physicians. Methods To assess the frequency and types of CAM therapy used by Hispanic and non-Hispanic white women and men with osteoarthritis, rheumatoid arthritis, or fibromyalgia, we used stratified random selection to identify 612 participants aged 1884 years and seen in university-based primary care clinics. Respondents completed an interviewer-administered survey in English or Spanish. Results Nearly half (44.6%) of the study population was of Hispanic ethnicity, 71.4% were women, and 65.0% had annual incomes of less than $25,000. Most (90.2%) had ever used CAM for arthritis, and 69.2% were using CAM at the time of the interview. Current use was highest for oral supplements (mainly glucosamine and chondroitin) (34.1%), mind-body therapies (29.0%), and herbal topical ointments (25.1%). Fewer participants made current use of vitamins and minerals (16.6%), herbs taken orally (13.6%), a CAM therapist (12.7%), CAM movement therapies (10.6%), special diets (10.1%), or copper jewelry or magnets (9.2%). Those with fibromyalgia currently used an average of 3.9 CAM therapies versus 2.4 for those with rheumatoid arthritis and 2.1 for those with osteoarthritis. Current CAM use was significantly associated with being female, being under 55 years of age, and having some college education. Conclusion Hispanic and non-Hispanic white arthritis patients used CAM to supplement conventional treatments. Health care providers should be aware of the high use of CAM and incorporate questions about its use into routine assessments and treatment planning.